2021
DOI: 10.1002/biot.202100046
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan and silver nanoparticles are attractive auxin carriers: A comparative study on the adventitious rooting of microcuttings in apple rootstocks

Abstract: Nanocarriers for encapsulation and sustained release of agrochemicals such as auxins have emerged as an attractive strategy to provide enhanced bioavailability and efficacy for improved crop yields and nutrition quality. Here, a comparative study was conducted on the effectiveness of chitosan‐as a biopolymeric nanocarrier‐ and silver‐as a metallic nanocarrier‐ on in vitro adventitious rooting potential of microcuttings in apple rootstocks, for the first time. Auxins indole‐3‐acetic acid (IAA) and indole‐3‐buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Due to its favorable physicochemical characteristics, including its excellent biocompatibility, low toxicity, biodegradability, and good solubility in water, this polymer has received a great deal of attention [7,8]. Additionally, the abundance of hydroxyl and amino groups in chitosan makes it possible to create nanoparticles through both chemical and physical crosslinking [9]. The pharmaceutical industry has shown a particular interest in chitosan and chitosan nanoparticles (Cs-NPs), notably for application in drug delivery systems that target specific delivery sites because they possess mucoadhesive properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its favorable physicochemical characteristics, including its excellent biocompatibility, low toxicity, biodegradability, and good solubility in water, this polymer has received a great deal of attention [7,8]. Additionally, the abundance of hydroxyl and amino groups in chitosan makes it possible to create nanoparticles through both chemical and physical crosslinking [9]. The pharmaceutical industry has shown a particular interest in chitosan and chitosan nanoparticles (Cs-NPs), notably for application in drug delivery systems that target specific delivery sites because they possess mucoadhesive properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…EN-IAA containing 15.88 and 166 μ g/mL of the IAA standard showed average sizes of 3.98 ± 0.160 μ m ( Figure 6(d) ) and 4.65 ± 0.076 μ m ( Figure 6(e) ), respectively. Several studies have shown that the increase in particle size is a consequence of IAA addition and effective encapsulation of this metabolite [ 24 , 51 ]. In addition, several clusters were observed, possibly related to a flocculation effect by the interaction of the charges because of the addition of the positive charge of IAA [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the efficiency of metallic carrier and polymer-based carrier for the delivery of auxins, IAA/indole butyric acid (IBA)-loaded silver NPs and chitosan NPs were synthesized via thermal reduction and ionic gelation methods, respectively. It was found that a nano-carrier system composed of AgNPs and chitosan can be an attractive carrier for auxin delivery (Korpayev et al, 2021).…”
Section: Encapsulation Methodsmentioning
confidence: 99%